PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MAGNETIC ADVENTURE BERBASIS ARTICULATE STORYLINE UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS V SDN KEDUNGBANTENG 01 TEGAL - Muhamad Zakiy I'shomuddin; Eka Titi Andaryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop the Magnetic Adventure interactive media based on Articulate Storyline to address low Science and Social Studies (IPAS) learning outcomes in fifth grade elementary students. The method used is Research and Development (R&D) with the ADDIE model, involving 24 students at SDN Kedungbanteng 01 as subjects. Instruments included expert validation, practicality questionnaires, and learning outcome tests (pretest-posttest). Validation and practicality results indicate the media is highly feasible for use. The effectiveness test proved a significant increase in the average student score from 57,77 to 75.83. N-Gain analysis yielded a score of 0.4393, which falls into the medium category. It is concluded that the Magnetic Adventure media is effective in improving elementary school students' IPAS learning outcomes.